Pengembangan Modul Ajar Matematika Berbasis Kurikulum Merdeka Pada Materi Aljabar - Fauzi, Moch. (RANGE: Jurnal Pendidikan Matematika, 2024)
This research aims to (1) produce a mathematics teaching module for class VII algebra material based on the independent curriculum that can improve the process, learning outcomes and students' love for the mathematics subject of algebra material, (2) be able to make students interested in learning mathematics, and (3) increase enthusiasm for learning and mastering the subjects you like, especially mathematics. The development model used in this research is adapting the ADDIE model, with stages (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The deployment stage was limited to the research location due to limited research time. The data analysis technique used is qualitative data analysis and quantitative data. From the research results, it is known that the development of an independent curriculum-based mathematics teaching module in class VII algebra material at SMP Ma'arif NU Darul Amin is valid and very good for improving learning outcomes. This is proven by the material expert validation results which obtained a score of 77.2%, including the feasible category, the media expert validation results obtained a score of 79.33%, including the appropriate category, the individual trial results obtained a score of 83.67%, including the very good category and the test results Trying a small group obtained a score of 87.33%, including the very good category